2013
DOI: 10.1037/lhb0000027
|View full text |Cite
|
Sign up to set email alerts
|

The expression and interpretation of uncertain forensic science evidence: Verbal equivalence, evidence strength, and the weak evidence effect.

Abstract: Standards published by the Association of Forensic Science Providers (2009, Standards for the formulation of evaluative forensic science expert opinion, Science & Justice, Vol. 49, pp. 161-164) encourage forensic scientists to express their conclusions in the form of a likelihood ratio (LR), in which the value of the evidence is conveyed verbally or numerically. In this article, we report two experiments (using undergraduates and Mechanical Turk recruits) designed to investigate how much decision makers change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 30 publications
(45 reference statements)
10
81
0
Order By: Relevance
“…The study did not compare responses to those from an alternative scale, but instead measured the extent of any divergence from a model in which intentions and perceptions align. Following previous work [5,6,7,8], this study provides additional evidence that the potential for miscommunication when verbal expressions are used and the perception problems observed suggest a number of divergences between the intended meaning of the expressions and the way in which they are perceived. The results and findings generated by this study highlight the need for the undertaking of further validation studies in alternative contexts.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The study did not compare responses to those from an alternative scale, but instead measured the extent of any divergence from a model in which intentions and perceptions align. Following previous work [5,6,7,8], this study provides additional evidence that the potential for miscommunication when verbal expressions are used and the perception problems observed suggest a number of divergences between the intended meaning of the expressions and the way in which they are perceived. The results and findings generated by this study highlight the need for the undertaking of further validation studies in alternative contexts.…”
Section: Discussionsupporting
confidence: 68%
“…In an investigation into the expression and interpretation of the verbal scale, Martire et al [7] undertook experiments that revealed evidence of a "weak evidence effect" whereby some participants inverted the direction of support when presented with evidence that provided weak support. Martire et al [8] explored different methods of communicating support.…”
Section: Introductionmentioning
confidence: 99%
“…Research has generally found that simulated jurors are less responsive to forensic evidence than Bayesian models indicate they should be (Thompson & Schumann, 1987;Faigman & Baglioni, 1988;Goodman, 1992;Smith et al, 1996;Schklar & Diamond, 1999;Nance & Morris, 2002, 2005Martire et al, 2013Martire et al, , 2014; for reviews of the early studies see Koehler, 2001;Kaye & Koehler, 1991;Thompson, 1989). But Thompson, Kaasa, and Peterson (2013) recently questioned whether jurors always underutilize forensic evidence relative to Bayesian norms.…”
Section: Logical Coherencementioning
confidence: 99%
“…This finding supports hypothesis 4 -that judgments of the chances of guilt made using the odds measure would be less responsive to the forensic evidence (lesser shifts in judgments) than judgments made using the log scale. Martire et al (2013Martire et al ( , 2014 reported that people sometimes give lower estimates of the odds of guilt after receiving forensic evidence that is characterized as weakly supportive of the prosecution (a finding they call the "weak evidence effect"). Our experiment had no conditions in which an expert characterized the forensic evidence as "weak," but we nevertheless found that a small percentage of our participants (7.6% for the Log scale; 6.4% for the Odds measure) judged the defendant less likely to be guilty after receiving the forensic evidence than before-in other words, they treated the forensic evidence as exculpatory.…”
Section: F3mentioning
confidence: 99%
See 1 more Smart Citation